Introduction to the Special Issue on Substance Use and Occupational Therapy - Emily F Rothman; Christine Jimenez (SAGE Publishing, 2023)
Readers of this journal are undoubtedly already aware that substance use disorders (SUDs) are a significant public health problem. More than 2% of the world population is living with a substance abuse disorder, and 1.4% of the global burden of disease is attributable to alcohol and illicit drug use. What readers may have had less opportunity to consider is that occupational therapists are an underutilized resource in our response to the substance use disorder crisis, and that occupational therapy researchers can provide key insights into the nature of substance use in individuals' lives and in our communities. That is the focus of this special issue.